Pemanfaatan Layanan Bimbingan dan Konseling dalam Pengoptimalan Keterampilan Mengingat Mahasiswa - Romi Fajar Tanjung (Institut Agama Islam Negeri Kerinci, Indonesia, 2019)
Skills are skills that need to be controlled so that any work or tasks that can be completed and achieve maximum results. A student needs to master many skills learned. One of the skills learned are skills of memory. Skills is very important considering ruled that any information received can be processed, stored and can be used when the information is needed. This study aims to identify the skills of memory students and analyze the utilization of counseling services in the optimization of skills given the student. The population of this research is student counseling Universitas Negeri Padang (UNP). The research sample is student counseling Universitas Negeri Padang (UNP) as many as 84 people. The sampling technique using simple random sampling. Collecting data using questionnaire instrument learning skills (memory). Data were analyzed using percentages with the help of Microsoft Exel. The research found that the skills of memory counseling students have not developed optimally. Thus, students need to seek out and study methods or techniques memory is good, so that any information received can be processed, stored and reused when the information is needed. The research found that the skills of memory counseling students have not developed optimally. Thus, students need to seek out and study methods or techniques memory is good, so that any information received can be processed, stored and reused when the information is needed. The research found that the skills of memory counseling students have not developed optimally. Thus, students need to seek out and study methods or techniques memory is good, so that any information received can be processed, stored and reused when the information is needed. Guidance and counseling to facilitate the students in considering the optimization skills of memory